Post COVID-19 Late Hemoptysis Managed with Bronchial Artery Embolization - Chataut, Dinesh; Ghimire, Prasoon; Suwal, Sundar; Thapa, Ajit (Nepal Journal of Medical Sciences, 2022)
SARS-COV-2 has been one of the most massive pandemics in modern history with typical radiological findings. As the follow up on patients who have survived this infection has been rising, newer studies have emerged detailing the long term sequelae of this disease and well as its complications. Few of the long term sequelae of COVID-19 pneumonia are lung fibrosis and bronchiectasis. Bronchiectatic changes in the lungs can lead to hemoptysis in the patient. We present you the case of a patient who recovered from COVID-19 pneumonia and presented with hemoptysis after 2 months secondary to bronchiectatic changes in lung fields. Patient underwent bronchial artery embolization as few studies have shown bronchial artery embolization to be effective and feasible management even on patients with history of COVID-19 pneumonia.